A new genetic variant of dengue serotype 2 virus circulating in the Peruvian Amazon. (July 2020) - Falconi-Agapito, Francesca; Selhorst, Philippe; Merino, Xiomara; Torres, Fiorella; Michiels, Johan; Fernandez, Connie; Talledo, Michael; Ariën, Kevin K.
Highlights: We report on a new dengue virus variant circulating in the Peruvian Amazon. Genotypic characterization of dengue virus is useful to monitor the distribution of circulating genotypes in endemic areas. Monitoring the introduction of new dengue virus strains helps to understand key drivers of dengue viral dynamics and epidemic patterns. Abstract: We sequenced the envelope gene of dengue virus serotype 2 (DENV-2-E) in samples from an outbreak reported in 2018, in Yurimaguas, Peru. The strain belongs to lineage 2 of the American/Asian genotype. We report a variant with two novel mutations (I379T and V484I) located in domain III of DENV2-E.